Conserving the Last Great Forests: A Meta-Analysis Review of the Drivers of Intact Forest Loss and the Strategies and Policies to Save Them - Scullion, Jason J.; Vogt, Kristiina A.; Drahota, Bethany; Winkler-Schor, Sophia; Lyons, Makaila (Frontiers in Forests and Global Change, 2019)
The conservation of Earth’s remaining intact forests (IFs) is a global priority, but improved understanding of the causes and solutions to IF loss is urgently needed to improve conservation efforts. This meta-analysis examines 207 case studies of IF loss occurring since 1970 to identify the multi-scale drivers of forest change and proposed case-specific solutions to IF loss. The goal of this study is to build a portfolio of conservation best practices for retaining IFs. The most frequently reported direct drivers of IF loss were logging, agriculture, ranching, and infrastructure expansion. Mining and fire were also prominent threats to IFs in selected areas. Indirect drivers of IF loss varied between continents, with high demographic pressures driving forest loss in Latin America, Asia, and Africa, contrasting with North America and Europe-Russia. Indirect economic and socio-political drivers were most frequently reported at the national scale for all continents studied, indicating a central role for national institutions in IF loss and conservation. Decisive socio-political factors underlying IF loss worldwide include political failures, institutional failures, and pro-development policies. A wide range of conservation interventions were recommended in the case studies. The proposed actions were most frequently within the forest, finance, and education and science sectors, and also emphasized inter-sectoral activities. Based on the results of this study, three core approaches to IF conservation that can be combined at the landscape scale are identified: protected areas, payments for ecosystem services, and agricultural reforms. Related enabling conditions include cooperative landscape management, effective enforcement, and political advocacy. The success of IF conservation efforts ultimately depends on sustained political support and the prioritization of high-value forest landscapes. Such efforts should mitigate socio-economic pressures through policy mixes that are cross-sectoral and place-based. Key policy priorities for IF conservation include addressing the systemic failures of public institutions, increasing political support for IF conservation, and countering harmful development activities.